Analisis Persiapan Dalam Perencanaan Pemekaran Desa Di Kabupaten Bulungan (Studi Kasus di Desa Tanjung Indah Lestari, Desa Bukit Indah, dan Desa Salimbatu Permai) - Budi Mulyadi; Ulung Pribadi (Journal of Governance and Public Policy, 2015)
An expansion of new village is hoped to be able to give positive effect to the society. However, structuring of expandedvillage, of course, has to do with regulations and rules recently. So, local government of Bulungan regency needs todo a good planning to expand Tanjung Indah Lestari village, Bukit Indah village, and Salimbatu Permai Village. Thepurpose of the research is: (1) to explain realization of expansion preparation to Tanjung Indah Lestari village, BukitIndah village, and Salimbatu Permai Village, based on the local rules of BUlungan regency number 4, 2011 aboutestablishment, abolition, annexation of a village and status change of a village becomes a political district, and (2) toexplain the factors which influence expansion realization to Tanjung Indah Lestari village, Bukit Indah village, andSalimbatu Permai Village. In this research, the writer applies qualitative approach. This research is done at Bulunganregency, especially in Tanjung Indah Lestari village, Bukit Indah village, and Salimbatu Permai Village. Data collecting isdone by interview, observation, and document analysis. The writer also applies qualitative descriptive analysis withdata reduction steps, data presentation, and data verification to the technique of data analysis. The result of thisresearch shows that the village chief and the society of Salimbatu Permai village have not understood concept of areaexpansion, purpose of expansion, and area expansion realization perfectly yet. If it is analyzed from the factors whichinfluence village expansion, so it may be conclude that Tanjung Indah Lestari village, Bukit Indah village, and SalimbatuPermai Village have been appropriate as a definitive village. If it is analyzed from the factors which influence villageexpansion, it may be concluded that Bukit Indah village is the most appropriate village to be expanded. On the otherhand, Tanjung Indah Lestari village is not still appropriate yet to be expanded. The inappropriate factors are communicationfactors among those villages and also means and infrastructure factors.